Applications of Hydroxyapatite-Based Polymeric Scaffolds in Bone Tissue Engineering: An Update - Nazanin Amiryaghoubi; Rana Jahanban Esfahlan (Advanced Pharmaceutical Bulletin)
Bone organ is comprised of an organic and inorganic environment, in which the collagen element and the mineral part are structured into spongy constructions. Hydroxyapatite (HAp) is the chief inorganic constituent of human bone. HAp is extensively utilized in bone tissue regeneration for its biocompatibility and a rising number of investigators are discovering ways to recover the physical belongings and biological roles of HAp. However, this biomimetic material indicates poor mechanical strength, for example, low tensile and compressive strength, which offer it inappropriate for bone tissue engineering. For this point, HAp is frequently utilized in a mixture with diverse polymers to increase their mechanical strengths and the general function of the implantable biomaterials advanced for orthopedic usage. In this review, we attempt to contribute a brief and inclusive outline of HAp-based natural and synthetic polymer materials to strengthen structures and their applications in bone tissue regeneration.